(untitled) (Communication & Society, 2021)
Artificial Intelligence (AI) is one of the most promising innovation frameworks with the potential to transform our relationship with technology. Particularly in journalism, AI is beginning to make its way transversally into the news production process and into the structure and functioning of the media. This article aims to anticipate how AI will impact on the Spanish media ecosystem and explain the medium-term transformations that are already being felt. The research approach is of an exploratory and descriptive nature, with a qualitative methodology based on Delphi-like in-depth interviews, encompassing an intentional sample of academic representatives, relevant associations and leading companies in the field of technology and communication. The results point out that AI will allow the extension of the current automated text news to audio and video on demand, it will favour that news can have a non-linear unstructured consumption, it will promote changes in the business model through new ways of relating with the audience and distribution of the product. Also, variations in the professional profile with a less operative journalist who will avoid routines –even of personal nature– that can be imitated by the machine and increase its cognitive contribution to the news production.